Answer:
I think the equation is 7l +5=60
Step-by-step explanation:
Answer:
c
Step-by-step explanation:
Answer:
The function is negative for all real values of x where -6< x < -2
Step-by-step explanation:
Given f(x) = (x + 2)(x + 6)
The graph of the function is as shown in the attached figure.
As shown, we can deduce the following:
The function is positive for all real values of x where x > -2 and x < -6
The function is zero at x = -2 and x = -6
The function is negative for all real values of x where -6 < x <-2
Compare the observations to the given statements:
So, The true statement is The function is negative for all real values of x where -6 < x <-2
The candle would be 4.5 inches tall after three hours.
9514 1404 393
Answer:
(2/3)(e^t +1)^(3/2)
Step-by-step explanation:
Use the substitution ...
u = e^t +1
Then du = e^t and you are finding the integral of ...
∫u^(1/2)·du
which you know by the power rule is ...
(2/3)u^(3/2) = (2/3)(e^t +1)^(3/2)